<< Chapter < Page Chapter >> Page >

Write each of the following products with a single base. Do not simplify further.

  1. k 6 k 9
  2. ( 2 y ) 4 ( 2 y )
  3. t 3 t 6 t 5
  1. k 15
  2. ( 2 y ) 5
  3. t 14
Got questions? Get instant answers now!

Using the quotient rule of exponents

The quotient rule of exponents allows us to simplify an expression that divides two numbers with the same base but different exponents. In a similar way to the product rule, we can simplify an expression such as y m y n , where m > n . Consider the example y 9 y 5 . Perform the division by canceling common factors.

y 9 y 5 = y y y y y y y y y y y y y y = y y y y y y y y y y y y y y = y y y y 1 = y 4

Notice that the exponent of the quotient is the difference between the exponents of the divisor and dividend.

a m a n = a m n

In other words, when dividing exponential expressions with the same base, we write the result with the common base and subtract the exponents.

y 9 y 5 = y 9 5 = y 4

For the time being, we must be aware of the condition m > n . Otherwise, the difference m n could be zero or negative. Those possibilities will be explored shortly. Also, instead of qualifying variables as nonzero each time, we will simplify matters and assume from here on that all variables represent nonzero real numbers.

The quotient rule of exponents

For any real number a and natural numbers m and n , such that m > n , the quotient rule of exponents states that

a m a n = a m n

Using the quotient rule

Write each of the following products with a single base. Do not simplify further.

  1. ( −2 ) 14 ( −2 ) 9
  2. t 23 t 15
  3. ( z 2 ) 5 z 2

Use the quotient rule to simplify each expression.

  1. ( −2 ) 14 ( −2 ) 9 = ( −2 ) 14 9 = ( −2 ) 5
  2. t 23 t 15 = t 23 15 = t 8
  3. ( z 2 ) 5 z 2 = ( z 2 ) 5 1 = ( z 2 ) 4
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Write each of the following products with a single base. Do not simplify further.

  1. s 75 s 68
  2. ( −3 ) 6 −3
  3. ( e f 2 ) 5 ( e f 2 ) 3
  1. s 7
  2. ( −3 ) 5
  3. ( e f 2 ) 2
Got questions? Get instant answers now!

Using the power rule of exponents

Suppose an exponential expression is raised to some power. Can we simplify the result? Yes. To do this, we use the power rule of exponents . Consider the expression ( x 2 ) 3 . The expression inside the parentheses is multiplied twice because it has an exponent of 2. Then the result is multiplied three times because the entire expression has an exponent of 3.

( x 2 ) 3 = ( x 2 ) ( x 2 ) ( x 2 ) 3  factors = ( x x 2  factors ) ( x x 2  factors ) ( x x 2  factors ) 3  factors = x x x x x x = x 6

The exponent of the answer is the product of the exponents: ( x 2 ) 3 = x 2 3 = x 6 . In other words, when raising an exponential expression to a power, we write the result with the common base and the product of the exponents.

( a m ) n = a m n

Be careful to distinguish between uses of the product rule and the power rule. When using the product rule, different terms with the same bases are raised to exponents. In this case, you add the exponents. When using the power rule, a term in exponential notation is raised to a power. In this case, you multiply the exponents.

Product Rule  Power Rule 5 3 5 4 = 5 3 + 4 = 5 7 but   ( 5 3 ) 4 = 5 3 4 = 5 12 x 5 x 2 = x 5 + 2 = x 7 but ( x 5 ) 2 = x 5 2 = x 10 ( 3 a ) 7 ( 3 a ) 10 = ( 3 a ) 7 + 10 = ( 3 a ) 17 but ( ( 3 a ) 7 ) 10 = ( 3 a ) 7 10 = ( 3 a ) 70

The power rule of exponents

For any real number a and positive integers m and n , the power rule of exponents states that

( a m ) n = a m n

Using the power rule

Write each of the following products with a single base. Do not simplify further.

  1. ( x 2 ) 7
  2. ( ( 2 t ) 5 ) 3
  3. ( ( −3 ) 5 ) 11

Use the power rule to simplify each expression.

  1. ( x 2 ) 7 = x 2 7 = x 14
  2. ( ( 2 t ) 5 ) 3 = ( 2 t ) 5 3 = ( 2 t ) 15
  3. ( ( −3 ) 5 ) 11 = ( −3 ) 5 11 = ( −3 ) 55
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

The sequence is {1,-1,1-1.....} has
amit Reply
circular region of radious
Kainat Reply
how can we solve this problem
Joel Reply
Sin(A+B) = sinBcosA+cosBsinA
Eseka Reply
Prove it
Eseka
Please prove it
Eseka
hi
Joel
June needs 45 gallons of punch. 2 different coolers. Bigger cooler is 5 times as large as smaller cooler. How many gallons in each cooler?
Arleathia Reply
find the sum of 28th term of the AP 3+10+17+---------
Prince Reply
I think you should say "28 terms" instead of "28th term"
Vedant
if sequence sn is a such that sn>0 for all n and lim sn=0than prove that lim (s1 s2............ sn) ke hole power n =n
SANDESH Reply
write down the polynomial function with root 1/3,2,-3 with solution
Gift Reply
if A and B are subspaces of V prove that (A+B)/B=A/(A-B)
Pream Reply
write down the value of each of the following in surd form a)cos(-65°) b)sin(-180°)c)tan(225°)d)tan(135°)
Oroke Reply
Prove that (sinA/1-cosA - 1-cosA/sinA) (cosA/1-sinA - 1-sinA/cosA) = 4
kiruba Reply
what is the answer to dividing negative index
Morosi Reply
In a triangle ABC prove that. (b+c)cosA+(c+a)cosB+(a+b)cisC=a+b+c.
Shivam Reply
give me the waec 2019 questions
Aaron Reply
the polar co-ordinate of the point (-1, -1)
Sumit Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask